Breve historia de la Olimpiada peruana de Química (1996-2010) - Chong, Miguel (Pontificia Universidad Católica del Perú, 2010)
The Peruvian Chemistry Olympiad (OPQ) is an annual competition that takes place in Peru since 1996 and consists on a competition among high school students. Around 1500 students from all over the country take part in this event.The winners gain access to international competitions such as the International Chemistry Olympiad (IChO) and the Latin American Chemistry Olympiad (OIAQ).Since 1999 the Peruvian participants have achieved important successes in international competitions. The OPQ is organized mainly by the lecturers, clerks and laboratory technicians from the Chemistry Section of the Pontificia Universidad Católica del Perú.

La Olimpiada Peruana de Química (OPQ) es una competición entre escolares que se realiza ininterrumpidamente en forma anual desde 1996. Participan alrededor de 1500 estudiantesa nivel nacional y los ganadores compiten en la Olimpiada Internacional de Química (IChO) y en la Olimpiada Iberoamericana de Química (OIAQ). Desde 1999 los ganadores de la OPQ han logrado diversos éxitos a nivel internacional. En su organización se encuentran comprometidos principalmente los docentes y personal técnico y administrativo de la Sección Química de la Pontificia Universidad Católica del Perú.
A short history of the Peruvian Chemistry Olympiad (1996-2010)
Keywords: Química; Olimpiadas científicas; Perú; https://purl.org/pe-repo/ocde/ford#1.04.00